In silico solvation free energy and thermodynamics properties of H2S in cholinium-based amino acid ionic liquids - Mohd Salehin, Fitri Norizatie; Jumbri, Khairulazhar; Ramli, Anita; Daud, Shaari; Abdul Rahman, Mohd Basyaruddin (Elsevier BV, 2019)
Solvation free energy ofH2S infive cholinium-based amino acid ILswas computed using Bennet Acceptance Ratio (BAR)method undermolecular dynamics (MD) simulation. Fromthe predicted free energy, degree of removal of acid gases in liquids system can be measured and quantified by looking at excess chemical potential (μex) and Henry's law constant (kH). In order to obtain accurate value of predicted free energy, the optimised potential for liquid simulation (OPLS) force field used was validated against experimental density. The predicted density of five cholinium-based amino acid ILs showed a great agreement with the experimental results showing percentage error of b3.0%. The lowest value of Henry's law constant (kH) of H2S was obtained by cholinium phenylalanate [Chl][PHY] (11.20 atm) while the highest value was 44.12 atm gained by cholinium serinate [Chl][SRI]. To support our understanding, the radial distribution function (RDF) of pure ILs and RDF for a specific atom of H2S in these ILs was evaluated. As observed, there were other factors that can affect the solubility of H2S in these ILs such as the length of alkyl chain of anion, interaction energy between cation and anion aswell as the hydrogen bonding interaction between polar sites of ILs with H2S molecules. Significantly, the longer hydrocarbon chain of anion, the weaker the interaction energy between the two ionic species. This in turn increases the free volume between the two ions and consequently promotes an excellent solubility of H2S in ILs. Furthermore, strong hydrogen bond interaction between the H2S and ILsmolecules also contributes to high solubility of H2S in this ionic environment.